Impact of Oil Price Fluctuations on Financial Markets since 2014 - Nguyen, Ha (World Bank, Washington, DC, 2017)
This paper investigates the causal impact of oil price fluctuations on financial markets since January 2014. Following a heteroscedasticity-based event study approach, the paper instruments changes in oil prices by exogenous shocks in oil supply. It finds that oil price declines raise uncertainty and hurt risky assets (U.S. stocks and high-yield corporate bonds) while lifting safe assets (U.S. investment-grade bonds and long-term Treasury bonds). In addition, lower oil prices boost the U.S. dollar and reduce the prices of emerging market equities. Remarkably, the declines in oil prices hurt several sectors that supposedly benefit from lower oil prices, such as basic materials, industrials, and transportation.